THE IMPACT OF WORK DISCIPLINE ON PERFORMANCE (Case Study of BPKP Representative Office of East Java Province) - Dwie Ratnauntarie; Achmad Daengs (Journal of Managerial Sciences and Studies, 2024)
The purpose of this thesis research is to obtain a clear picture of the variables of absence, awareness of responsibility and willingness to obey regulations that affect employee performance at the Representative Office of the Financial and Development Supervisory Agency (BPKP) of East Java Province. The problem in this study is whether there is an influence between the variables of absence, awareness of responsibility and willingness to obey regulations that have a simultaneous and partial effect on employee performance. This study uses a random sampling technique, where samples were taken as many as 50 employees with the hope that they can truly represent all employees at the Representative Office of the Financial and Development Supervisory Agency (BPKP) of East Java Province. The method of data collection was carried out by distributing questionnaires. From the results of the SPSS analysis, it shows that there is a strong and positive relationship between employee discipline and performance, as evidenced by the determinant coefficient (R²) which shows a value of 0.262, this means that the contribution affects the employee performance variable by 26.2%. Likewise, the absence variable (X) which has a dominant influence on performance (variable Y), this shows that the influence between employee discipline and performance has a strong and positive influence, where increasing employee attendance will be followed by increased performance, this is evidenced by the large β Standard of 0.299 and t count 2.332 is greater than the other t counts. Thus a brief description of this thesis, the author presents in this abstract with the hope that it will be useful for readers, in general and especially for the BPKP Representative of East Java Province.